An Analysis of Code-switching by El Barack on TikTok Video - ita, Ita Rosita; Novari, Ari Fajria; Rohimajaya, Nur Azmi (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2025)
This research focused on analysis of types and functions of code-switching used by El Barack in TikTok videos. Ten samples of TikTok videos from the @inijedar channel featuring El Barack, the writers applied poplack theory which functioned to categorize the types of code-switching, and Gumperz which functioned to explain what are function used by El Barack on TikTok video. This research also adopted descriptive-qualitative methods. Data collection was carried out using observation, documentation and checklists. This research focuses on speeches containing code switching produced by El Barack. The conclusions obtained regarding all data, Subjects A4 to A10, have types of Code-switching, but subjects A1 to A3 do not have one of the types of Code-switching, this is proven by data analysis on videos: subjects A1 to A10, have a total of 58 types of code-switching, and also have a total of 58 functions of code-switching.